Siciological Aspect of The Novel “Rasa” By Tere Liye - Oktasari, Jesika; Triyadi, Slamet; Mujtaba , Sahlan (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2025)
This study aims to (1) describe the structure of the novel Rasa by Tere Liye, (2) explain the social aspects in the novel Rasa by Tere Liye (a review of the sociology of literature), (3) the relevance of the research results as teaching materials for novels in high school. Qualitative descriptive research with the object of research in the form of social aspects in the novel Rasa by Tere Liye (a review of the sociology of literature). The research data is in the form of discourse in the novel Rasa by Tere Liye. The secondary data sources for the study are in the form of theses, author biographies, and the internet. Data collection techniques are using library techniques, observing, and taking notes. The results of the study are as follows: (1) the structure of the novel Rasa by Tere Liye shows the life journey of a high school teenager named Linda with various feelings of hatred, heartache, disappointment, and sincerity in her life. The plot used in this novel is a mixture. The main character is Linda. The settings in the novel Rasa include time setting, place setting, and social setting. (2) Analysis of social aspects in the novel Rasa by Tere Liye is as follows: the language system used is non-formal, the knowledge system in this novel comes from digital and scientific knowledge, the social system is social class and social relations. The system of life equipment comes from computers and lessons at school, the livelihood system comes from working as an editor, and the belief system is by worshiping God Almighty.